INTESTINAL PROTOZOAN PARASITES OF Oreochromis niloticus OF DADIN KOWA DAM, YAMALTU DEBA L.G.A OF GOMBE STATE - I, ZAINAB.; F.A, UMAR; .A.G, NURU; M., KABIRU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
Fishes are greatly affected by many parasites causing diseases or harm to the fish. Parasitic protozoans are among these organisms that infect fish and other aquatic organisms. The parasitic protozoans were investigated in Oreochromis niloticus from Dadin-Kowa Dam. Fifty (50) fish was collected, weighed and the sexes were identified by observing the genitals. After dissecting the fish, the gut contents of each was emptied in to a container with 0.9% of saline solution. A small portion of the sample was taken and observed under microscope. Out of the 50 sample, 43 (86%) were not infected by any protozoan parasite while 7(14%) were infected with protozoan parasites (Cryptobia iubians and Ichthyophthirius multifiliis). Females (14.79%) harbour the parasites more than the males (13.28%) and the fishes with higher weight have more parasites load when compared with the smaller fishes. At the end of the research two protozoa parasites were identified in the intestinal tract of Oreochromis niloticus from Dadin-kowa reservoir.